2005
DOI: 10.1021/jm050136d
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Highly Potent Adenosine Deaminase Inhibitors Containing the Pyrazolo[3,4-d]pyrimidine Ring System. Synthesis, Structure−Activity Relationships, and Molecular Modeling Studies

Abstract: This study reports the synthesis of a number of 1- and 2-alkyl derivatives of the 4-aminopyrazolo[3,4-d]pyrimidine (APP) nucleus and their evaluation as inhibitors of ADA from bovine spleen. The 2-substituted aminopyrazolopyrimidines proved to be potent inhibitors, most of them exhibiting K(i) values in the nanomolar/subnanomolar range. In this series the inhibitory activity is enhanced with the increase in length of the alkyl chain, reaching a maximum with the n-decyl substituent. Insertion of a 2'-hydroxy gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 54 publications
1
58
0
Order By: Relevance
“…The structure of these drugs, including EHNA, resembles Ado, the endogenous substrate of the enzyme. Docking of EHNA to the ADA crystal structure revealed that the Ade NH 2 group formed a hydrogen bond with Asp 295 and 296, while the 2´-hydroxy group formed a hydrogen bond with the N hydrogen of His 17 and the S hydrogen of Cys 153 [326]. Modifications of the structure of EHNA using the 1-and 2-alkyl derivatives of the 4-aminopyrazolo [3,4-d]pyrimidine nucleus (Fig.…”
Section: Recently Developed Drugs Acting On the Adenosinergic System mentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of these drugs, including EHNA, resembles Ado, the endogenous substrate of the enzyme. Docking of EHNA to the ADA crystal structure revealed that the Ade NH 2 group formed a hydrogen bond with Asp 295 and 296, while the 2´-hydroxy group formed a hydrogen bond with the N hydrogen of His 17 and the S hydrogen of Cys 153 [326]. Modifications of the structure of EHNA using the 1-and 2-alkyl derivatives of the 4-aminopyrazolo [3,4-d]pyrimidine nucleus (Fig.…”
Section: Recently Developed Drugs Acting On the Adenosinergic System mentioning
confidence: 99%
“…Modifications of the structure of EHNA using the 1-and 2-alkyl derivatives of the 4-aminopyrazolo [3,4-d]pyrimidine nucleus (Fig. 4C) also led to potent inhibitors of ADA [326]. Structure-based drug design and metabolic considerations led to the development of additional non-nucleoside ADA inhibitors ( Fig.…”
Section: Recently Developed Drugs Acting On the Adenosinergic System mentioning
confidence: 99%
“…The set of KIEs for the three ADAs were determined under competitive conditions. The intrinsic [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] N], [6-13 C], and [6- 30 Adenylate kinase (AK), pyruvate kinase (PK), hexokinase, and bovine spleen adenosine deaminase (BtADA) were purchased from Sigma. Phospho-D-ribosyl-1-pyrophosphate (PRPP) synthase and adenine phosphoribosyltransferase (APRTase) were purified according to the methods reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent progress has been reported by Terasaka et al and by some of us who have developed a new generation of nonnucleoside ADA inhibitors (II, III, and IV in Fig. S1) (6)(7)(8)(9)(10)(11). Unfortunately, the understanding at molecular level of the ligand/ADA interaction is hampered by the pronounced ability of the active site to accommodate different inhibitors and by the crucial role played by water molecules during ligand binding.…”
mentioning
confidence: 99%